Graft preservation with heparinized blood/saline solution induces severe graft dysfunction - Veres, Gábor; Hegedűs, Péter; Barnucz, Enikő; Zöller, Raphael; Klein, Stephanie; Radovits, Tamás; Korkmaz-İçöz, Sevil; Karck, Matthias; Szabó, Gábor (Interactive cardiovascular and thoracic surgery, 2015)
AbstractOBJECTIVES. Vascular grafts are often stored in cold physiological saline/heparinized blood preservation solution. Until now, only in vitro studies inv
Gesehen am 08.07.2020